Information Transfer: A listening comprehension technique from oral texts to diagrammatic texts - García Botero, Natalia; Marín Abondano, Paloma (Universidad Pontificia Bolivariana, 2018)
This paper focuses on the Information Transfer Technique to enhance listening skill in English learning as a second language. It comprises two aspects which are input and output. The former -input- refers to oral texts that students interpret through Bottomup and Top-down processes; these processes involve the identification of specific and contextual parameters of the speech. The latter -output- is associated with the production of graphic texts which show the development of meaning from the messages. Altogether, this article advocates the aforementioned technique to English learners as a meaningful way to improve their listening comprehension.

El artículo presenta la técnica Información Transfer como una estrategia para mejorar la habilidad de escucha en el aprendizaje del inglés como segunda lengua, la cual involucra dos aspectos importantes: input y output. En este caso, el input está dado por textos orales que se exploran a través de los procesos de Bottom-up y Topdown mediante el reconocimiento de elementos específicos y contextuales del discurso. Por su parte, el output hace alusión a la producción del lenguaje escrito por medio de herramientas gráficas que demuestran la construcción de significado en torno a los textos orales analizados. En efecto, la técnica se da a conocer para que los aprendices del inglés interesados en mejorar su comprensión auditiva se valgan de ésta para lograrlo.
6 páginas
Keywords: Técnica de Transferencia de Información; Escucha dinámica; Escucha activa; Bottom-up; Top-down; Textos gráficos